Understanding national-government policies regarding globalization: A trade-finance analysis - Asaf Razin (Journal of Government and Economics (JGE), 2022)
Why different national governments have different policies regarding globalization? This is an important research topic of government and economics. In the paper, I analyze how different income groups have different attitudes towards globalization; and how such attitudes shape government policy. A standard example is that more openness in trade benefits the owners of a country's abundant factor, while reducing the income of the owners of the scarce factor. Welfare-state policy depends on which income group is politically dominant. The paper adopts the framework of a small open economy trading in goods and financial securities with the rest of the world, to provide a general-equilibrium analysis of income-based globalization attitudes for national welfare-state government policies. The analysis shows that different income groups have varied attitudes towards globalization, depending on trade-related and macro-related fundamentals. They are: (i) the degree of trade border frictions, (ii) the degree of international finance frictions, (iii) the relative factor abundance that determines the capital intensity of the country's exports; and, (iv) the domestic saving propensity on one hand, and the productivity of domestic investment, on the other hand-determining whether the country is a financial capital exporter or importer.
Keywords: 330